(3CSS GdJMdjd GdQjGVj (B/s - (3efUhQ, YhVs; (3YRGe, UHQjs ((3YeGf(B: s (3OGQ eQhGf ddfTQ(B, s, 1992)
(3GdfgGjGJ,GdGJUGd,GdGJUGd GdefJXe hGdGbJQGfGJ GdhJjQjI,GdGTJbGb,JcGed QjeGfs
(3HHdjhZQGajG(B:(3U(B.197s
Keywords: (3GdJMdjd GdQjGVjs